Usages et représentations de l’orthographe française - Bernadette Wynants (La Bretagne Linguistique, 1998)
In modern times, spelling has been constructed as an institution, i.e. as a set of norms developed through social activity, subject to spatial and temporal extension, which contribute to the production and reproduction of a coherent social system, modern France. Today, spelling is a source of contradiction and conflict. Spelling is no longer a principle of unity but of heterogeneity.